A molecular phylogeny of the genus Psittacula sensu lato (Aves: Psittaciformes: Psittacidae : Psittacula , Psittinus , Tanygnathus , † Mascarinus ) with taxonomic implications - Braun, Michael P.; Sauer-Gürth, Hedwig; Wink, Michael (Zootaxa, 2019)
The long-tailed parakeets of the genus Psittacula Cuvier, 1800 have thus far been regarded as a homogeneous and monophyletic group of parrots. We used nucleotide sequences of two genetic markers (mitochondrial CYTB, nuclear RAG-1) to reconstruct the phylogenetic relationships of Psittacula and closely related species. We found that the Asian genus Psittacula is apparently paraphyletic because two genera of short-tailed parrots, Psittinus Blyth, 1842 and Tanygnathus Wagler, 1832, cluster within Psittacula, as does †Mascarinus Lesson, 1830. To create monophyletic genera, we propose recognition of the following genera: Himalayapsitta Braun, 2016 for P. himalayana, P. finschii, P. roseata, and P. cyanocephala; Nicopsitta Braun, 2016 for P. columboides and P. calthrapae; Belocercus S. Müller, 1847 for P. longicauda; Psittacula Cuvier, 1800 for P. alexandri and P. derbiana; Palaeornis Vigors, 1825 for †P. wardi and P. eupatria; and Alexandrinus Braun, 2016 for P. krameri, †P. exsul, and P. (eques) echo. Additionally, Psittacula krameri and P. alexandri are paraphyletic species, which should be split to form monophyletic species.
Gesehen am 27.03.2019